Vaccinoprophylaxis of infections and activity of immuno-inflammatory rheumatic diseases: pro et contra - B. S. Belov; N. V. Muravyeva (Антибиотики и Химиотерапия)
In modern conditions, patients with immuno-inflammatory rheumatic diseases (IIRD) are at significant risk of influenza, pneumococcal and herpes viral infections, as well as COVID-19, in some cases fatal. The most effective way to prevent infectious diseases and reduce mortality from them is vaccination, which is recommended in the inactive phase of IIRD. However, a number of patients with IIRD have a refractory course of the disease, and achieving remission in them turns out to be a difficult task, and therefore the problem of vaccination of such patients against the background of an active inflammatory process is very relevant. The review analyzes data on the use of vaccine prophylaxis for the above infections in the active phase of IIRD. In the vast majority of cases, vaccination was safe and did not lead to an exacerbation of IIRD or the development of new autoimmune phenomena.